(3QSGdI aj GdeLGR GddZhjs - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3HNW GdeDdas)
(3ChdgG (B:s
(3hHYO aEfc SCdJ Yf eYfi bhdge GdeLGR (B((3cPG bQCJgG(B) (3hGdeLGR HeQJjf hCQOJ TQM Pdc hHjGfg aGYde HGQc Gddg ajce hCbQ Hce GdYjfCf eKd bhdfG GdeTaiEdN gh (B() (3aj GdCUd GSe dEMOi TaJj GdHYjQ GdeJOdjIs
(3BNQgG (B:s
(3hgh fbdg Yf eYfGg(B() (3jdGFe GdeSJYGQ efg Edi eYfi jYeg hjYe GdeSJYGQ dg dYdGbI GdJbjjO Ke fbd ef gPG GdeYfi GdYGe Edi edGFe GdeSJYGQ dg HNUhUg dYdGbI GdEWdGb hGdJbjjO aGage gPg GdMceI aEfgG VGdI GdeDefs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdHdGZIs